On a Structural Approach to the Complex Systems Conceptual Modeling - Brodsky, Yury I. (2023 International Conference on Control, Artificial Intelligence, Robotics & Optimization (ICCAIRO), 2023)
Conceptual modeling is gaining an essential role in designing large-scale systems, especially as the complexity of the latter increases. The design tool for such systems is the development of ontologies for their subject areas. A problem arises: in our activity, we consider more complex subject areas, and the complexity of ontologies is growing. Is there a limit to this complexity? The design of large-scale systems is already suffocating with complexity - it is difficult to describe the components of the domain, their synthesis is complicated, and even more difficult is the software implementation of the model within the framework of an imperative, object-oriented approach. Debugging the created software system is extremely difficult. The structural theory offers a unified way to describe the subject areas of a broad class of large-scale systems, realizing in this description the principle of "One in everything and all in One." Based on this, an end-to-end technology of reporting, synthesis, and software implementation of models of complex, large-scale systems, which is close to CAD methods, is being built. In implementing a software system, it is possible to remain within the framework of declarative programming, avoiding imperative programming, which significantly simplifies its debugging.